ANALISIS PRODUKTIVITAS PENGELOLAAN ZAKAT DARI SISTEM BAGI HASIL (Studi Kritis Bank Muamalat Cabang Kota Jayapura) - Eko Siswanto (Palita: Journal of Social Religion Research, 2018)
The position of zakat in Islam is very important in order to maintain the existence of Islam and the ummah. So serious is the position of this zakat, so that at the beginning of the Caliphate of Abu Bakr al-Siddiq there were people who carried out defiance to pay zakat, therefore the Caliph carried out ijtihad by fighting them. This shows the commitment of Islam in tackling the poor in a sustainable and systematic manner. To accommodate the large number of dlu'afa people, at the present time the ilin amilin are making efforts by channeling zakat in productive forms. This article aims to analyze the productivity of zakat management from the profit sharing system at Bank Muamalat Kota Jayapura. The study was conducted in a juridical-normative manner, in addition to reviewing the productivity analysis of zakat management from the profit sharing system at Bank Muamalat Kota Jayapura. The research approaches used include: theological approaches, sociological approaches, philosophical approaches. The results showed that the profit sharing system used at Bank Muamalat Kota Jayapura Branch was the main contract a / -musyarakah and al-mudharabah. The profit sharing system at Bank Muamalat Kota Jayapura Branch through Baitul Maal Muamalat (BMM) was limited to the distribution of basic necessities for the dluafa and orphans, the SBL program (Sahur berbuka and Lebaran) in the form of basic food packages 300.000 rupiahs per package, and Lebaran packages of 300.000 rupiahs in the form of cash and prayer equipment.